Production Process and Quality Testing of Arabica Ground Coffee (Coffee arabica L) Solok Regency, West Sumatera - Rince Alfia Fadri; Kesuma Sayuti; Novizar Nazir; Irfan Suliansyah (Politeknik Pertanian Negeri Payakumbuh, 2020)
One of the types of coffee cultivated in Solok Regency is Arabica Coffee (Coffea Arabica L). The quality of the coffee produced can be influenced by the proper harvesting and post-harvest process so as to produce ground coffee with good quality. This research is done by the method of observation, descriptive, and hedonic test. Ground coffee produced in Solok Regency has a semi-mechanical harvesting process while the post-harvest process begins with the release of the skin and meat of the fruit, subsequent drying, and release of the skin of horns, sorting and grading, roasted, milling and packaging. This research aims to study the processing and quality of Arabica Ground Coffee in Solok Regency.